2004
DOI: 10.1158/1078-0432.ccr-04-0083
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Ranging Study of the Safety and Pharmacokinetics of Atrasentan in Patients with Refractory Malignancies

Abstract: Purpose: Atrasentan is an orally bioavailable selective antagonist of the endothelin receptor ET A . Due to the potential activity of this agent against prostate cancer, the majority of subjects enrolled in prior studies had been male. This Phase I study sought to determine the toxicity and pharmacokinetics of daily atrasentan in a population of both female and male subjects with advanced malignancies.Experimental Design: Patients with refractory malignancies received atrasentan once daily at doses ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 17 publications
(15 reference statements)
3
22
0
Order By: Relevance
“…This finding is consistent with previous knowledge that docetaxel does not induce or inhibit CYP3A4, the major CYP450 involved in the metabolism of atrasentan [17-18]. Furthermore, atransentan pharmacokinetic parameters observed on this study were similar to those reported using the drug as a single agent in both volunteers and patients with cancer [19-21]. …”
Section: Resultssupporting
confidence: 92%
“…This finding is consistent with previous knowledge that docetaxel does not induce or inhibit CYP3A4, the major CYP450 involved in the metabolism of atrasentan [17-18]. Furthermore, atransentan pharmacokinetic parameters observed on this study were similar to those reported using the drug as a single agent in both volunteers and patients with cancer [19-21]. …”
Section: Resultssupporting
confidence: 92%
“…The safety profile of atrasentan in these patients was consistent with that observed in healthy volunteers and prostate cancer patients, even at the higher doses in this study, and it reflects the physiologic antagonism of ET A receptors. 13,21 The two patients with partial responses and several patients with prolonged stable disease reflect similar activity rates as those seen in relief of cancer pain and reduction in prostate-specific antigen and other tumor markers in prostate cancer. 22 In addition, the 6-month PFS rate of 13% in patients with GBM is comparable to previous phase II studies of cytotoxic chemotherapy in recurrent GBM, but with less toxicity.…”
Section: Discussionmentioning
confidence: 82%
“…Similar moderate binding parameters and energetics of many established drug molecules to serum albumin have been observed, suggesting that A8HQ can be a good example to understand the binding mode of similar drug candidates. Since the B isomer of HSA predominates under increased Ca 2+ concentration in blood plasma, it has been suggested that N-B transition has physiological significance (Ryan et al 2004). Increase in the association constant of the B isomer can modify its distribution and bioavailability in the body, and therefore this study also provides information about the dose-response relationship and rate of elimination of drugs derived from hydroxyquinoline in patients with increased Ca 2+ blood plasma concentration.…”
Section: Discussionmentioning
confidence: 91%